PERBEDAAN PENGARUH PEMBERIAN MINYAK KELAPA SAWIT (Palm Oil) DAN MINYAK KELAPA MURNI (Virgin Coconut Oil) TERHADAP PERBAIKAN PROFIL LEMAK (KOLESTEROL) PADA TIKUS DENGAN DIET ATEROGENIK - Kusumastuty, Inggita; Andarini, Sri; Anom Aswin, Anak Agung Gede (Fakultas Kedokteran Universitas Brawijaya, 2006)
Virgin Coconut Oil (VCO) is a kind of coconut oil that most of its contained is Medium Chain Fatty Acids (MCFA) andÂ previous stdy showed that MCFA has an ability to prevent vascular desease. This experiment was done to Â prove theÂ ability of virgin coconut oil to reduce cholesteroltotal of rats with atherogenic diet compared with palm oil. This experimentÂ was designed as true pre test post test experiment with control groups. The number of samples were 24 male wistar ratsÂ and they were separated into 4 treatment groups in Â which each of them has 2 diet sections. The First section was doneÂ within 8 weeks, group A got normal diet, group B, Cand D got atherogenic diet with lard, after this section finished all ofÂ the groups got cholesterol pre test level. The next 4 weeks, in the second section treatment diet, group A got normal diet,Â group B got atherogenic diet with lard, group C gotatherogenic diet with palm oil and group D got atherogenic diet withÂ virgin coconut oil, after the second section was over rat cholesterol levels were measured by enzymatic photometric testÂ base on â€œCHO-PAPâ€. The results from One Way Anova which was continued to Tukey test showed that group B,C and DÂ were homogenous, but they were different significantly againts group A on pre test with p(0.001) < 0.05.